Parameters for assessing housing quality for the elderly: a literature review - Souza, Rayane Barcellos Marinho de; Fontes, Maria Solange Gurgel de Castro; Magagnin, Renata Cardoso (National Journal of City Management, 2020)
The phenomenon known as increased life expectancy is triggered by changes in the age pyramid and points to a demand for studies focused on the well-being and quality of life of the elderly, with the housing unit being one of the main factors of performance in the quality of life for this age group. In this context, questions arise such as: what are the influences of housing conditions on the quality of life of the elderly? And what are the main parameters for assessing housing quality for senior citizens? Given this context, this article aims to identify, through a systematic literature review, which are the main parameters for assessing housing quality for the elderly. The methodology consisted of surveying studies on this topic in digital databases that incorporated the variables: sociodemographic, technical-functional aspects, technical-constructive aspects and behavioral and psychological aspects, in relation to the analysis parameters. These aspects point to a series of housing quality indicators for the elderly, and the highlight is: the perception of quality and housing situation, accessibility, social relationships. The results show that the housing quality for this age group is associated with a correlation between factors, especially accessibility, the relationship with the surroundings and the layout of the environments, thus an integrative analysis of the characteristics of the project, construction, social use and housing surroundings is necessary.